Modern Electroencephalographic Assessment Techniques Theory and Applications - Sakkalis, Vangelis.; Sakkalis, Vangelis. (Neuromethods, 2015)
Modern Electroencephalographic Assessment Techniques: Theory and Applications presents numerous signal processing and connectivity analysis methodologies addressing a wide variety of clinical applications including epilepsy, schizophrenia, Alzheimer’s disease, and even alcoholism. Among the different topics addressed, the neurophysiological basis of cognitive processes is also investigated. The goal is to provide a comprehensive overview of the most modern and widely established approaches mainly applied in, but not limited to, decomposing high resolution multichannel Electroencephalography (EEG) and Magnetoencephalography (MEG) signals into functional interconnected brain regions. Synergistic approaches linking both EEG/ MEG and functional Magnetic Resonance Imaging (fMRI) techniques are also discussed. In line with the popular Neuromethods series, chapters present the theoretical basis of each method along with prosperous application domains, in the form of a balanced mixture of theoretical tutorials, comprehensive reviews, and original research. Emphasis is given to the underlying assumptions, to technical matters that greatly affect the outcome of each proposed method, to the ambitions, and to the domain of application of each method. Furthermore, links to graph theory and visualization of connectivity motifs is also addressed in an attempt to better describe the functional characteristics of brain networks.   Authoritative and practical, Modern Electroencephalographic Assessment Techniques: Theory and Applications touches upon both the biomedical and computational aspects of this exciting and rapidly evolving field, and will allow for a more in-depth, vital understanding of the brain’s complex underlying mechanisms.